2020
DOI: 10.1080/19336896.2020.1761515
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Chinese patients with sporadic Creutzfeldt-Jakob disease

Abstract: Sporadic Creutzfeldt-Jakob disease (sCJD) is a rare, incurable, and fatal neurodegenerative disorder. The objective of this study was to describe the clinical features and survival time of Chinese sCJD patients, and to explore the associations between clinical data and survival. In this study, we analysed the clinical data of 21 sCJD patients in a tertiary care hospital and used all Chinese case material available from 152 patients with sCJD in literatures between 2008 and 2018. The mean age of onset of all 17… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 32 publications
2
7
0
Order By: Relevance
“…In this study, we found that there were more female than male sCJD patients, and the female-to-male ratio was 1.39. Two studies of Chinese patients were consistent with our findings, in which the number of females predominated (10,12), but two other studies had reported a higher proportion of males, where the female-to-male ratio was 0.82 and 0.79, respectively (8,14). Because of small sample size and various nationalities in China, there might be biases in those results.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In this study, we found that there were more female than male sCJD patients, and the female-to-male ratio was 1.39. Two studies of Chinese patients were consistent with our findings, in which the number of females predominated (10,12), but two other studies had reported a higher proportion of males, where the female-to-male ratio was 0.82 and 0.79, respectively (8,14). Because of small sample size and various nationalities in China, there might be biases in those results.…”
Section: Discussionsupporting
confidence: 90%
“…Besides, the fear and limited understanding of prion disease, as well as the restriction on the conditions of medical institutions, also affect autopsies on patients with this contagious neurodegenerative disease in China. Biopsy could not be performed smoothly and generally in China, either, which was confirmed by previous domestic literature (8,(10)(11)(12)(13). Thus, their vast majority of molecular pathological subtypes remained unknown.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…According to Yang et al study of 173 sCJD cases, extrapyramidal symptoms were noticed in over 77% of patients and were the second most frequent symptom after progressive dementia. [19].…”
Section: Discussionmentioning
confidence: 99%
“…Knowledge of factors relating to survival might prove helpful in predicting the course of the disease, guiding clinical management and decision-making, and assessing the effectiveness of possible future treatments. To our knowledge, there are few studies on TSE survival ( Puopolo et al, 2003 ; Pocchiari et al, 2004 ; Sanchez-Valle et al, 2004 ; Heinemann et al, 2007 ; Nagoshi et al, 2011 ; Iwasaki et al, 2015 ; Sun et al, 2020 ; Yang et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%